Pembelajaran STEM di Queensland Australia - Wijokongko Wijokongko (Ideguru: Jurnal Karya Ilmiah Guru, 2019)
STEM learning in Australia has been well implemented and inspires Indonesian teachers to have great experiences. In Australia, STEM is considered as an learning approach and development that integrates the interrelated of science, technology, engineering, and mathematics. The aim of the paper is to give a brief description of the implementation of STEM in Australia, the condition of transportation, the characteristic of people, as the result of observation during a short course in Australia. The result of the observation shows that STEM has been well implemented. The school has implemented STEM for their frame work. The school collaborate with the universities and industries to support their students in doing research. STEM can use 5E (Engage, Explore, Elaborate, Explain, Evaluate). The transportation system and the social relationship provide the Indonesian teachers to get good ones. The way of thinking , the education system, and the development of technology in schools can be valuable and great possibilities to implement in Indonesia. Other advance countries has implemented STEM. Indonesia should implement STEM to support the success of the students among the 21th century and the revolution 4.0 era.